Implementation of Waiter Service Standard Operating Procedures (SOP) in Improving Service Effectiveness at Boulevard Bistro Restaurant, Lion Hotel & Plaza Manado - Diva Maria Ransun; Mikhael Credo Samuel Mangolo; Mercy A. Lumare (Faculty of Economics and Business, University of Mataram, 2025)
This study aims to examine the implementation of Standard Operating Procedures (SOPs) in improving the effectiveness of waiter service and to identify the challenges encountered at Boulevard Bistro Restaurant, Lion Hotel & Plaza Manado. The research employed a descriptive qualitative method with data collected through observation, interviews, and literature review. Informants included the Head Chef, Restaurant Coordinator, and waitstaff directly involved in SOP implementation. The study was conducted from July 2024 to April 2025. The findings show that SOPs have been consistently applied in technical aspects such as punctuality, order accuracy, and service sequence indicating a strong procedural discipline among staff. However, inconsistencies were found in the soft skills dimension, particularly friendliness, proactive communication, and guest engagement, which are critical to enhancing service effectiveness. Operational challenges were also observed, including limited equipment availability and increased workload during peak hours, which constrained full adherence to SOPs. The study concludes that while the technical application of SOPs is well established, improvements in behavioral aspects, staff training, and supervisory consistency are essential to achieve comprehensive service quality and guest satisfaction.